Model struktural kelembagaan rantai pasok pada klaster keripik kentang menggunakan interpretive structural modelling - Nadya Prabaningtias; Siti Asmaul Mustaniroh; Wike Agustin Prima Dania (AGROINTEK, 2024)
Batu City is one of the potential centers of agroindustry SMEs based on local wisdom to become superior regional products contributing to the economy and community empowerment. Potato chips are one of Batu City's regional superior products that have been clustered into 2 Micro and Small scales based on indicators of turnover, production capacity, number of workers, length of operation, and halal certification. The contribution of the potato chip SME cluster is essential in evaluating the structural performance of supply chain institutions to increase the efficiency of integration of upstream and downstream actors. The research aims to develop a structural model of supply chain institutions in the Potato Chips SME Cluster. The research method uses Interpretive Structural Modeling (ISM), which is relevant to the complexity of the supply chain. The object of research involved three actors of the potato chip SME cluster, including raw material suppliers, micro and small cluster SMEs, and distributors. The results showed that the key structural elements in micro-cluster SMEs include low labor skills; diversity in raw material quality; implementation of labor training and development activities; labor training and development on GHP, GMP, and production SOPs; improvement of labor skills and SME productivity; and collaborative relationships between supply chain actors. Structural key elements in small cluster SMEs include low labor capability; implementation of labor training and development activities; provision of supply chain information systems; labor training and development on GHP, GMP, and production SOPs; improvement of product quality standards and periodic evaluation of the 3 supply chain flows; improvement of labor skills and SME productivity; and sustainable collaborative relationships between supply chain actors. Both SME clusters involved 3 supply chain actors as key elements of the involved institutions.